Near‐infrared light is neuroprotective in a monkey model of Parkinson disease. Issue 1 (12th December 2015) - Darlot, Fannie; Moro, Cécile; El Massri, Nabil; Chabrol, Claude; Johnstone, Daniel M.; Reinhart, Florian; Agay, Diane; Torres, Napoleon; Bekha, Dhaïf; Auboiroux, Vincent; Costecalde, Thomas; Peoples, Cassandra L.; et al.
Abstract : Objective: To examine whether near‐infrared light (NIr) treatment reduces clinical signs and/or offers neuroprotection in a subacute 1‐methyl‐4‐phenyl‐1, 2, 3, 6‐tetrahydropyridine (MPTP) monkey model of Parkinson disease. Methods: We implanted an optical fiber device that delivered NIr (670nm) to the midbrain of macaque monkeys, close to the substantia nigra of both sides. MPTP injections (1.5–2.1mg/kg) were made over a 5‐ to 7‐day period, during which time the NIr device was turned on. This was then followed by a 3‐week survival period. Monkeys were evaluated clinically (eg, posture, bradykinesia) and behaviorally (open field test), and their brains were processed for immunohistochemistry and stereology. Results: All monkeys in the MPTP group developed severe clinical and behavioral impairment (mean clinical scores = 21–34; n = 11). By contrast, the MPTP‐NIr group developed much less clinical and behavioral impairment (n = 9); some monkeys developed moderate clinical signs (mean scores = 11–15; n = 3), whereas the majority—quite remarkably—developed few clinical signs (mean scores = 1–6; n = 6). The monkeys that developed moderate clinical signs had hematic fluid in their optical fibers at postmortem, presumably limiting NIr exposure and overall clinical improvement. NIr was not toxic to brain tissue and offered neuroprotection to dopaminergic cells and their terminations against MPTP insult, particularly in animals that developed few clinical signs. Interpretation: Our findings indicate NIr to be an effective therapeutic agent in a primate model of the disease and create the template for translation into clinical trials. ANN NEUROL 2016;79:59–75